The Effectiveness of Storytelling Module in Improving Daycare Educators’ Confidence and Proficiency in Storytelling in English - Wan Jumani, Fauzi; Noor Raha, Mohd Radzuan; Ezihaslinda, Ngah; Fatimah, Ali; Noor Azlinda, Zainal Abidin; Anita, Abdul Rani; Haslinda, Hashim; Airin, AbdulGhani (American Scientific Publishers, 2018)
As a step to improve the level of English among Malaysians, it is believed that English should be exposed to children as early as 0–3 years, and not introduced at the kindergarten ages of 4–6 which is the current practice in the Malaysian education curriculum. However, at daycare level, where children of working parents spend at least an average of 8 hours a day, many of the daycare educators are secondary school leavers with basic English language proficiency. In order for the children to acquire a new language, the daycare educators themselves have to first be fluent, proficient and confident in using the target language. Hence, a knowledge transfer programme with 30 daycare educators under Pahang Daycare Providers Association was kickstarted with the aim to develop and harness English communication skills through two modules: Communication English and Effective Storytelling Techniques. This paper focuses on the storytelling module, its approaches to enhance daycare educators’ confidence and proficiency and discusses the effectiveness of this module based on the perceptions of the daycare educators who participated in the knowledge transfer programme.